(untitled) (Fiep Bulletin - online, 2012)
The aim of this study was to determine the levels of body composition, strength and power in athletes of karate, and verify that inflences the adiposity levels in muscular streght. Nine athletes of karate (intermediate ans advanced) participated in this stydy, with 27,8 ± 13,9 years old. We evaluated anthropometric variables: body composition, strength, flexibility and Power. We conducted percetage and descriptive (mean, standart deviation) statistical analysis and Spearman test (p<0,05). The levels of strehgth and are composition are as expected for the population. However, they could be decreased levels of % fat and fat mass. Levels of adiosity were related inversely with the strength.